Effect of Temperature and Pressure on the Density of Organic Waste Briquettes - Riky Satria; Yolli Fernanda; Refdinal Refdinal; Sri Rizki Putri Primandari (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
Organic waste is one way of utilizing biomass to produce energy. The advantage of biomass is that it tends to be renewable. The energy from biomass that will be used to make briquettes is processed and compressed into a more regular form with a high calorific value. This research will involve organic waste as a source of biomass. To obtain briquettes that are dense, tight, and in good condition, tests were conducted with various temperature and pressure settings. Organic waste with particle size between 18 and 30 mesh is used in this method. Briquetting using heat-treated molds, with temperatures of 200, 250 and 300 °C with a holding time of 5 minutes and also applying pressures of 5 MPa, 10 MPa, 15 MPa and 20 MPa. At 300 °C, 10 and 20 MPa pressure, the briquettes were dense, tight and had high density values. Sampah organik merupakan salah satu cara pemanfaatan biomassa untuk menghasilkan energi. Keuntungan dari biomassa adalah bahwa hal itu cenderung diperbaharui. Energi dari biomassa yang akan digunakan untuk membuat briket diolah dan dikompresi menjadi bentuk yang lebih teratur dengan nilai kalor yang tinggi. Penelitian ini akan melibatkan limbah sampah organik sebagai sumber biomassa. Untuk mendapatkan briket yang padat, rapat, dan dalam kondisi baik, dilakukan pengujian dengan berbagai pengaturan suhu dan tekanan. Sampah organik dengan ukuran partikel antara 18 dan 30 mesh digunakan dalam metode ini. Pembriketan menggunakan cetakan yang diberi panas, dengan suhu 200, 250 dan 300 ℃ dengan waktu penahanan 5 menit dan juga pemberian tekanan 5 MPa, 10 MPa, 15 MPa dan 20 MPa. Pada suhu 300 °C, tekanan 10 dan 20 MPa dihasilkan briket yang padat, rapat dan memiliki nilai densitas yang tinggi.